Pollutants in particulate and gaseous fractions of ambient air interfere with multiple signaling pathways in vitro - Novák, Jirí; Jálová, Veronika; Giesy, John P; Hilscherová, Klára (Environment international, 2009)
Traditionally, contamination of air has been evaluated primarily by chemical analyses of indicator contaminants and these studies have focused mainly on compounds associated with particulates. Some reports have shown that air contaminants can produce specific biological effects such as toxicity mediated by the aryl hydrocarbon receptor (AhR) or modulation of the endocrine system. This study assessed the dioxin-like toxicity, anti-/estrogenicity, anti-/androgenicity and anti-/retinoic activity of both the particulate and gas phase fractions of air in two regions with different types of pollution sources and a background locality situated in an agricultural area of Central Europe. The first region (A) is known to be significantly contaminated by organochlorine pesticides and chemical industry. The other region (B) has been polluted by historical releases of PCBs, but the major current sources of contamination are probably combustion sources from local traffic and heating. Samples of both particle and gas fractions produced dioxin-like (AhR-mediated) activity, anti-estrogenic and antiandrogenic effects, but none had any effect on retinoid signaling. AhR-mediated activities were observed in all samples and the TEQ values were comparable in both fractions in region A, but significantly greater in the particulate fraction in region B. The greater AhR-mediated activity corresponded to a greater coincident antiestrogenicity of both phases in region B. Our study is the first report of antiestrogenicity and antiandrogenicity in ambient air. Anti-androgenicity was observed in the gas phase of all regions, while in the particulate phase only in one region due to the specific type of pollution in that area. Even though based on concentrations of individual compounds, except for the OCPs, the level of contamination of the two regions was similar, there were strong differences in responses in the bioassays between the two regions. Moreover, AhR-mediated activity and antiestrogenic potencies were greater in region B, where the pollution level according to the chemical analysis was similar or less than in the other region, which indicates the presence of other atmospheric pollutants with specific effects. The results document the advantage and utility of the simultaneous use of bioassays and chemical analysis in risk assessment of complex environmental samples.
Keywords: Cell Line; signální transdukce; Rats; látky znečišťující vzduch; Air Pollutants; dioxiny; Česká republika; antagonisté androgenů; Signal Transduction; endokrinní disruptory; Czech Republic; krysa rodu Rattus; antagonisté estrogenu; Tretinoin; Estrogen Antagonists; Endocrine Disruptors; zvířata; Humans; zeměpis; Androgen Antagonists; buněčné linie; Dioxins; Geography; tretinoin; lidé; Animals